Inventory of Mothering and Fathering Activism for More Sustainable Living Environments - Rodela, Romina (Södertörn University, 2023)
This datafile contains information about movements at a global scale, that were identified as being composed mainly by mothers, fathers and others who have close connections with youth and children, on behalf of whom they seek and demand change.

The data summarized in this file is about groups, movements and organizations made up in large extent of mothers who in that role engage in activism and related activities in the public sphere.

Denna datafil innehåller information om rörelser i global skala, som identifierats som huvudsakligen sammansatta av mödrar, fäder och andra som har nära kopplingar till ungdomar och barn, på uppdrag av vilka de söker och kräver förändring.

Uppgifterna som sammanfattas i denna fil handlar om grupper, rörelser och organisationer som i stor utsträckning består av mammor som i den rollen ägnar sig åt aktivism och relaterade aktiviteter i det offentliga rummet.
Inventering av Mothering and Fathering-aktivism för mer hållbara livsmiljöer
Keywords: ENVIRONMENT; MILJÖ; ENVIRONMENTAL CHANGES; MILJÖFÖRÄNDRINGAR; WELL-BEING (SOCIETY); VÄLBEFINNANDE (SOCIALT); social change; social förändring; social movements; sociala rörelser; mothering activism; mammaaktivism; Political behaviour and attitudes; Politiska beteenden och attityder; Gender and gender roles; Kön och könsroller; Youth; Ungdomar; Children; Barn; Social behaviour and attitudes; Socialt beteende och attityder; Cultural activities and participation; Kulturaktiviteter och deltagande; Social change; Social förändring; Social Work; Socialt arbete; Social and Economic Geography; Social och ekonomisk geografi; Human Geography; Kulturgeografi